Evaluation of Green Open Space Policy in Supporting Sustainable Development - Onasis, Andi; Akib, Haedar; Niswaty, Risma; Wahira; Kasmawati, Andi (Journal of Indonesian Scholars for Social Research, 2025)
Green Open Space (GOS) plays a crucial role in promoting environmental sustainability, enhancing urban resilience, and improving the quality of life in cities. This study evaluates the effectiveness of green open space policies in supporting sustainable development, focusing on policy implementation, challenges, and best practices. Using a mixed-methods approach, this research examines policy frameworks, land-use regulations, and urban planning strategies in selected cities. Key indicators such as green space coverage, ecological benefits, and social inclusion are analyzed to assess the impact of GOS policies. The findings highlight disparities between policy objectives and actual implementation, emphasizing governance challenges, land-use conflicts, and financial constraints. Furthermore, the study identifies innovative approaches, including smart green infrastructure and community-based green space management, as potential solutions for optimizing GOS policies. The research concludes that a more integrated and adaptive policy approach is essential to enhance the effectiveness of green open spaces in achieving sustainable urban development. Recommendations include strengthening policy enforcement, increasing stakeholder collaboration, and leveraging technology for better monitoring and planning.